AN ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING NOUNS AND PRONOUNS FOR GRADE VIII STUDENTS AT SMP MUHAMMADIYAH 12 PERUMNAS MAKASSAR - Uzlifatil Jannah Binti Samir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the difficulties of Grade VIII students at SMP Muhammadiyah 12 Perumnas Makassar in learning nouns and pronouns and the factors influencing them. Using a descriptive quantitative design, 18 students from class VIII A participated. Data were collected through a grammar test and a questionnaire. Results show that students struggle to distinguish nouns and pronouns, identify their types, and use them correctly in sentences, except for reflexive pronouns. Contributing factors include neutral motivation, grammatical complexity, limited practice, and lack of learning support. Project-based, interactive, and technology-assisted strategies are recommended to enhance understanding and engagement.